Mobilization and Export of Particulate and Dissolved Solids and Organic Carbon From Contrasting Mountainous River Watersheds in California and Oregon. Issue 4 (5th April 2023) - Goñi, Miguel A.; Welch, Kylie A.; Ghazi, Layla; Pett‐Ridge, Julie C.; Haley, Brian A.
Abstract: Concentration‐discharge ( C ‐ Q ) relationships of total suspended solids (TSS), total dissolved solids (TDS), particulate organic carbon (POC), and dissolved organic carbon (DOC) were investigated in the tributaries and main‐stems of two mountainous river systems with distinct watershed characteristics (Eel and Umpqua rivers) in Northern California and central Oregon (USA). Power‐law ( C = a × Q b ) fits to the data showed strong transport‐limited behavior ( b > 1) by TSS and POC, moderate transport limitation of DOC ( b > 0.3) and chemostatic behavior ( b < 0) by TDS in most streams. These contrasts led to significant compositional differences at varying discharge levels, with particle‐bound constituents becoming increasingly important (relative abundances of 50% to >90%) at high‐flow conditions. Organic carbon contents of TSS displayed marked decreases with discharge whereas they increased in TDS during high‐flow conditions. Daily and cumulative material fluxes for different coastal streams were calculated using the C ‐ Q relationships and showed that the delivery of transport‐limited constituents, such as TSS and POC (and DOC to a lesser degree), was closely tied to high‐discharge events and occurred primarily during the winter season. The coherence between winter fluxes and high wave‐southerly wind conditions along the coast highlights how seasonal and inter‐annual differences in fluvial discharge patterns affect the fate of land‐derived materials delivered to coastal regions. Plain Language Summary: Rivers play a key role in transporting materials from land to the ocean. In this study, we investigated several streams of different characteristics from two basins, the Eel River in Northern California and the Umpqua River in central Oregon. We measured how the concentrations of dissolved and particulate materials, including total suspended and dissolved solids and particulate and dissolved organic carbon, varied as a function of river flow. Our results show that different streams export these materials in different ways depending on the level of river flow and certain watershed characteristics. The different trends with river flow exhibited by these constituents impact the total amounts exported by rivers each year as well as the timing of their export. The latter is important because ocean conditions off the Eel and Umpqua rivers exhibit marked contrasts in winds, currents, and waves depending on the season. In the paper, we explore how the combination of the timing of export by the river and the ocean conditions offshore influences the distribution and cycling of particulate and dissolved materials from land in the coastal ocean. Key Points: Concentration‐discharge relationships for different constituents show marked variability among streams from different watersheds Total suspended solids, particulate organic carbon, and to a lesser degree, dissolved organic carbon exhibit transport limitation The magnitude and composition of constituent fluxes display variability at distinct time scales that affect their transport to the ocean